CD69 flow cytometry to complement interferon‐γ release assay for active tuberculosis - Kim, Yoonjung; Han, Man‐Hoon; Kim, Shin‐Woo; Won, Dong Il (Cytometry. Part B, Clinical cytometry, 2022)
Background The interferon‐γ (IFN‐γ) release assay (IGRA) is widely used to diagnose tuberculosis (TB) caused by Mycobacterium tuberculosis (Mtb). However, indeterminate IGRA results due to “high Nil” or “low PHA” responses limit its clinical utility. We developed a novel assay using CD69 flow cytometry (FC) to complement IGRA. Methods CD69 FC measures the surface CD69 expression on T cells prior to centrifugation to harvest the plasma for IGRA. T cell responses against Mtb antigen 1 (Ag1) or Ag2 were measured using three‐color FC (CD3, CD4, and CD69) in TB (n = 140) and non‐TB groups (n = 117). The cutoff values of Δ%CD69bright cells (stimulated minus unstimulated) for CD4+ and CD4− T cells were established based on healthy individuals (n = 63). The assay performances of CD69 FC and IGRA were compared. Results In subjects with determinate IGRA results (“positive” or “negative”; n = 216), the diagnostic accuracies of CD69 FC (90.3%) and IGRA (87.0%) were not significantly different (p = 0.31). For indeterminate IGRA results (n = 40), CD69 FC attained a diagnostic accuracy of 92.5%. The CD4+/CD4− ratio within CD69bright T cells measured by CD69 FC was significantly higher (p < 0.05) in the active TB group (6.39 ± 132.05; n = 72) than in other CD69 FC‐positive subjects (2.84 ± 15.36; n = 63) (p < 0.05), whereas CD8 responses expected by IGRA (difference of IFN‐γ levels between Mtb Ag tubes) did not differ significantly (0.00 ± 9.18 and 0.00 ± 4.25, respectively, IU/ml; p = 0.58). Conclusions We demonstrated the potential of CD69 FC as a simple, rapid assay for clarifying indeterminate IGRA results and identifying active TB. With further improvements, CD69 FC may complement the IGRA to enhance TB risk stratification in the routine diagnostic workup.